Problems and prospects of sustainable development of the transport industry of Ukraine - Kersys, Robertas; Pererva, P. G. (Видавництво "Фенікс", 2024)
The report proves that the sustainable development of the transport sector in Ukraine requires a comprehensive approach, including infrastructure modernization, the introduction of innovative technologies, reducing environmental impact and integration with international transport systems. The development of these areas will improve the quality of transportation, improve the environmental condition and economic growth of the country.
Проблеми та перспективи сталого розвитку транспортної галузі України
Keywords: sustainable development; transport industry; innovative technologies; environment; efficiency